Prinsip Kehati-hatian dalam Penerbitan Sertifikat Hak Atas Tanah yang Sedang dalam Sengketa Pada Program PTSL - Putri Saleh, Tasya Aisyah (UNES Law Review, 2023)
There are still many land disputes in Indonesia and the government is implementing a PTSL program to ensure legal certainty of land rights. It cannot be denied that negligence can occur when the government continues to issue land title certificates when the land is still in dispute, so the goal of legal certainty will not be achieved. This research raises two problem formulations, the principle of caution in issuing land rights certificates that are in dispute under the PTSL program, and the responsibility of BPN for issuing land right certificates that are in dispute. This research is normative research, with a statutory regulation approach, and used secondary data, namely primary legal materials in the form of statutory regulations, secondary legal materials are from books and journals, and tertiary legal materials is legal dictionaries. The research show that the application of the precautionary principle is realized by implementing administration based on information, complete documents and prepared with care and thoroughness. BPN is responsible for through land administration actions of issuing decisions to cancel legal products in accordance with PTUN decisions which have permanent legal force and can be subject to administrative sanctions and the imposition of compensation.